Stoichiometric Equilibrium Model Based Assessment of Hydrogen Generation through Biomass Gasification. (2016) - George, Joel; Arun, P.; Muraleedharan, C.
Abstract: Hydrogen produced from renewable energy sources is clean and sustainable. Biomass gasification has a significant role in the context of hydrogen generation from biomass. Assessment of the performance of biomass gasification process regarding the product gas yield and composition can be performed using mathematical models. Among the different mathematical models, thermodynamic equilibrium models are simple and useful tools for the first estimate and preliminary comparison and assessment of gasification process. A stoichiometric thermodynamic equilibrium model is developed here, and its performance is validated for steam gasification and air-steam gasification. The model is then used to assess the feasibility of different biomass feedstock for gasification based on hydrogen yield and lower heating value.